Honour is in contentment life before oil in Ras al-Khaimah (UAE) and some neighbouring regions - Lancaster, William 1938-; Lancaster, Fidelity (Studien zur Geschichte und Kultur des islamischen Orients.Beihefte zur Zeitschrift "der Islam",, 2011)
Based on interviews and field research, the authors explore the sets of ideas Arab tribespeople from Ras Al-Khaimah had about tribe and community; social and economic networks, and jural contracts for livelihoods and profits; their uses of their environments; the moral relations of credit, debt and labour; ruling; economic and political transformations; and ideas of regional history where conflicts were regarded as disputes over sets of ideas, and informal accounts of tribal and local histories. Published sources give a wider context to these ideas and events which show the great complexity and differing perspectives of 'life before oil' in the Gulf